INTEGRATION OF STATE AUDIT IN THE EAEU COUNTRIES - Zhagalbayeva Meruyert; Shakharova Aliya (Research Retrieval and Academic Letters, 2023)
Against the background of instability of the world economy, a certain stagnation of the world economy, integration has become an important driver of growth for our countries. It is necessary to develop methods aimed at a pragmatic and constructive policy of cooperation aimed at protecting international interests in the international arena without prejudice to national sovereignty. The author of the article analyzed the activities of the supreme financial control bodies of the countries of the Eurasian Economic Union, and also assessed the activities of the state audit bodies of the Republic of Kazakhstan as a member of the EAEU.